Maternal sleep and small for gestational age infants in the Japan Environment and Children’s Study: a cohort study - Morokuma, Seiichi (BMC Res Notes, 2017)
OBJECTIVES: Small for gestational age infants have an increased risk of immediate complications, short-term morbidity and mortality, and long-term neurologic and metabolic disorders in adulthood. Previous research has shown that reduced sleep duration is a risk factor for SGA birth. However, only a few studies have evaluated maternal sleep as a risk factor for SGA birth. In the present study, we investigated the relationship between the amount and quality of mothers’ sleep and infants’ birth weight. RESULTS: This cohort study (n = 8631) used data from the Japan Environment and Children’s Study, an ongoing cohort study that began in January 2011. Data on sleep status (sleep duration and one indicator of sleep quality) and potential confounding factors were recorded. A log-binomial regression model was used to estimate the risk of small for gestational age birth, and the results were expressed as risk ratios and their respective 95% confidence interval. No significant results were observed for sleep duration or tiredness upon waking. Neither the amount nor the quality of mothers’ sleep was associated with the risk of small for gestational age birth.